Emotional Intelligence and Prosocial Behavior in College Students: A Moderated Mediation Analysis - Wang, Haiying; Wu, Shuang; Wang, Weichen; Wei, Chao (Frontiers in Psychology, 2021)
The current study examined the relationship between emotional intelligence and pro-social behavior and construct a model by examing the mediating effect of social support and the moderating effect of self-esteem in this relationship. 742 college students completed Emotional Intelligence Scale, Prosocial Tendencies Measurement Scale-Chinese Version, Perceived Social Support Scale, and Self-esteem Scale. Results indicated that: (1) Emotional intelligence positively predicted prosocial behavior. (2) Social support partially mediated the relationship between emotional intelligence and prosocial behavior. (3) Self-esteem moderated the direct effect of emotional intelligence on prosocial behavior and the relationship between social support and prosocial behavior. That is, when the self-esteem of college students is higher, the promotion effect of social support on prosocial behavior is enhanced. These findings showed that high emotional intelligence was conducive to improving social support, and then promoting prosocial behavior, and high self-esteem of individuals would increase the positive role of emotional intelligence. This study verified the combined effect of external and internal factors on prosocial behavior, which had a certain guiding significance for the cultivation of prosocial behavior in college students.